2016
DOI: 10.1039/c5dt03609g
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Triphenylphosphinine and 2,4,6-triphenylposphabarrelene revisited: synthesis, reactivity and coordination chemistry

Abstract: The synthesis of 2,4,6-triphenylphosphinine has been revisited and a general protocol for the preparation of such low-coordinate phosphorus compounds in good to excellent yields could be established. This allows to investigate several aspects of the chemistry of 2,4,6-triarylphosphinine, such as the reaction with in situ generated benzyne to give 2,4,6-triphenylphosphabarrelene. The corresponding 2,4,6-triphenylphosphabarrelene-selenide could be characterized crystallographically for the first time and the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Alternatively, we found that 12 can also be obtained quantitatively from the corresponding phosphabarrelene-selenide 13, as this compound was converted to 12 within 1.5 h upon irradiation with UV light. 17 The transformations described above are summarized in Scheme 2.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, we found that 12 can also be obtained quantitatively from the corresponding phosphabarrelene-selenide 13, as this compound was converted to 12 within 1.5 h upon irradiation with UV light. 17 The transformations described above are summarized in Scheme 2.…”
mentioning
confidence: 99%
“…The relevant IR-spectroscopic data (ñ A 1 ) of this series of Ni(0) complexes are summarized in Table 1, with Ph 3 PNi(CO) 3 (17) as the reference compound. As expected, the aromatic 2,4,6-triphenylphosphinine 7 is the best p-acceptor with the lowest net-donor capability, while phosphabarrelene 6 is a somewhat better s-donor.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Mathey and co-workers have demonstrated the synthesis of 2-(2-pyridyl)­phosphinines and their coordination chemistry toward Group 9 and 10 metals . Muller’s group has synthesized λ 3 -phosphinines that bears a 2-pyridyl group via the corresponding pyrylium salt, and their unique emission behavior has also been disclosed . In addition, the transformation into λ 5 -phosphinines and their photophysical properties have been reported .…”
Section: Introductionmentioning
confidence: 99%